A study of an efficient scheduling algorithm for simultaneous 5G multimedia Traffic - Mohd Ramli, Huda Adibah; Abdalla Hashim, Aisha Hassan; Mohamed Rasied, Thaahirah Shireen; Asnawi, Ani Liza; Abdul Rahman, Farah Diyana (Institute of Electrical and Electronic Engineers, Inc., 2022)
Simultaneous support for Fifth Generation (5G) multimedia traffic in time-changing and frequency-varying downlink channels is a challenging task given their stringent and competing desired Quality of Service (QoS). Packet scheduling is essential in the 5G network for delivering multimedia packets to the end users whilst simultaneously meeting their required QoS. An abundant number of packet scheduling algorithms have been developed. Yet, the performance of these packet scheduling algorithms in the downlink 5G, which has a different framework and characteristics may require further investigations. Moreover, most 5G packet scheduling algorithms support only one multimedia use case. Therefore, the performance of several legacy packet scheduling algorithms for simultaneous support of 5G multimedia traffic in the downlink 5G is investigated in this paper. An array of simulation was conducted, and the results demonstrate the efficiency of a packet scheduling algorithm comes at the expense of the degradation of another network metric. Therefore, network operators need to decide on which metric to be optimized when choosing a packet scheduling algorithm to be implemented in their networks.